Physiological and Molecular Basis of Dormancy in Yam Tuber: A Way Forward towards Genetic Manipulation of Dormancy in Yam Tubers (Global Journal of Science Frontier Research, 2022)
Yam Dioscorea sps holds a key position among the staple food crops of Africa and possess better organoleptic properties compared to cassava potato within Solanum spp and sweet potato Ipomoea batatas L Lam Yam tubers are reported to be rich in steroidal C27 saponins and diosgenin which makes it as a crop of choice for the industrial production of pregnenolone-derived steroids However prolonged tuber dormancy spanning between 120 - 180 days after physiological maturity remains a challenge for yam improvement and production This poses a serious threat to food security and yam industry Furthermore limited research efforts and low investment aggravates the slow progress in yam improvement Deciphering the physiological and molecular factors involved in the regulation of tuber dormancy in yams will permit genetic manipulation of desired traits in yam This requires thorough understanding of the physiological and molecular mechanisms regulating tuber dormancy in yam The present review provides an overview on the basic hormonal biosynthetic signaling pathways sugar signaling pathways and the cross talk between them which provides vital insights into mechanisms regulating yam tuber dormancy
Keywords: yam tuber; dormancy; physiology; molecular; hormones; sugars -metabolism